4D printing of high performance shape memory polymer using stereolithography. (15th July 2017) - Choong, Yu Ying Clarrisa; Maleksaeedi, Saeed; Eng, Hengky; Wei, Jun; Su, Pei-Chen
Abstract: High shape fixity, shape recovery, and prolonged shape memory cycle life are desirable aspects of 4D printed parts; however, the durability of 4D printed parts is rarely investigated. Here, we demonstrated a photopolymer printable by stereolithography apparatus (SLA) which uses a tBA- co -DEGDA network based on dual-component phase switching mechanism to build parts of complex geometries and exhibit shape memory behavior. The material can achieve a high curing rate and precise printing that are highly desired for SLA process. The mechanical strength of the printed parts is comparable statistically to industrial SMPs and shape memory tests showed excellent shape memory performance with higher durability of > 20 shape memory cycles as compared to current 4D printed parts. This work is believed to enable the use of SLA technology to fabricate responsive components of high performance, which also significantly advances the 3D printing technology for more robust applications. Graphical abstract: Highlights: A dual-component mechanism was used to synthesize SMPs for stereolithography process. Approach for material evaluation and process optimization are proposed. Developed SMPs is readily polymerized at rapid laser curing speed with high accuracy. High shape fixity, shape recovery and long shape memory cycle life achieved by SLA SMPs. Robust performance addresses mechanical degradation issue in current 4D printed parts.